Establishment and application of a root wounding–immersion method for efficient virus-induced gene silencing in plants - Li, Xinyun; Tao, Na; Xu, Bin; Xu, Junqiang; Yang, Zhengan; Jiang, Caiqian; Zhou, Ying; Deng, Minghua; Lv, Junheng; Zhao, Kai (Frontiers in Plant Science, 2024)
In the post-genomic era, virus-induced gene silencing (VIGS) has played an important role in research on reverse genetics in plants. Commonly used Agrobacterium-mediated VIGS inoculation methods include stem scratching, leaf infiltration, use of agrodrench, and air-brush spraying. In this study, we developed a root wounding-immersion method in which 1/3 of the plant root (length) was cut and immersed in a tobacco rattle virus (TRV)1:TRV2 mixed solution for 30 min. We optimized the procedure in Nicotiana benthamiana and successfully silenced N. benthamiana, tomato (Solanum lycopersicum), pepper (Capsicum annuum L.), eggplant (Solanum melongena), and Arabidopsis thaliana phytoene desaturase (PDS), and we observed the movement of green fluorescent protein (GFP) from the roots to the stem and leaves. The silencing rate of PDS in N. benthamiana and tomato was 95-100%. In addition, we successfully silenced two disease-resistance genes, SITL5 and SITL6, to decrease disease resistance in tomatoes (CLN2037E). The root wounding-immersion method can be used to inoculate large batches of plants in a short time and with high efficiency, and fresh bacterial infusions can be reused several times. The most important aspect of the root wounding-immersion method is its application to plant species susceptible to root inoculation, as well as its ability to inoculate seedlings from early growth stages. This method offers a means to conduct large-scale functional genome screening in plants.